Decomposing the gender wage gap: An analysis of the tourism sector at the European level. - Marfil-Cotilla, Marina; Campos-Soria, Juan Antonio; Ribeiro, Alector; García-Pozo, Alejandro (My University, 2026)
Studies carried out in different countries show that workers in the tourism sector face unfavourable labour and pay conditions and a significant gender wage gap, which shows that this is an international phenomenon. However, this matter has only been studied at national level in specific countries, such as Spain, the United Kingdom, Norway, Portugal, or Brazil, among others (Burgess, 2003; Dashper, 2019; Guimarães and Silva, 2016; Santos and Varejão, 2007; Skalpe, 2007; Santero, Segovia, Castro, Figueroa and Talón, 2015; Oliver and Sard, 2020; Thrane, 2008). However, to our knowledge, no international comparisons have been carried out to explain the heterogeneity of the gender wage gap across countries and its main determinants. We have not found any studies that analyse what part of this cross-country heterogeneity could be explained by the contextual, economic, and institutional conditions of each country, as well as by factors that particularly affect the tourism sector at the international level, such as educational mismatch, labour mobility or occupational segregation, among others. This paper uses a micro and macro perspectives simultaneously, through a multilevel approach, which may be helpful for understanding how the characteristics of the employees of each country and how the country characteristics can affect the differences at European level in the gender wage gap and its discriminatory component in the tourism sector. We created a combined dataset, based on the latest EU Structure Earnings Survey (SES-2018), that contains matched employer-employee data in the EU-28 countries, with country-level contextual variables obtained from other international statistical sources.
Keywords: Transversalidad de género - Salarios, etc.; Gender wage gap; Discriminatory component; Hierarchical linear models; Tourism